PENTINGNYA SUSTAINABILITY DALAM MENINGKATKAN PERFORMA PERUSAHAAN - Arifin (Jurnal Mahkota Bisnis (Makbis), 2024)
In recent decades, the market has become increasingly competitive, making it more challenging for businesses to achieve economic goals. At the same time, the pressure to achieve and maintain environmental sustainability has also risen. This study examines the factors influencing economic goals as well as the relationship between economic and environmental goals. There are innovation, customer focus, supplier relationships, network maturity, and strategic that will be the factors of economic sustainability. The study also demonstrates that both economic and environmental goals have a substantial impact on growth and that sustainability is essential for companies to ensure their long-term viability. Sustainability of company will be one of the factors of increasing company’s performance in financial and non financial.